High-Resolution Mapping and Dynamics of the Transcriptome, Transcription Factors, and Transcription Co-Factor Networks in Classically and Alternatively Activated Macrophages - Das, Amitabh; Yang, Chul-Su; Arifuzzaman, Sarder; Kim, Sojin; Kim, Sun Young; Jung, Kyoung Hwa; Lee, Young Seek; Chai, Young Gyu (Frontiers in Immunology, 2018)
Macrophages are the prime innate immune cells of the inflammatory response, and the combination of multiple signaling inputs derived from the recognition of host factors (e.g., interferon-g/IFN-γ) and invading pathogen products (e.g., TLR agonists) are required to maintain essential macrophage function. The profound effects on biological outcomes of inflammation associated with IFN-γ pretreatment (“priming”) and TLR4 ligand bacterial LPS-induced macrophage activation (M1 or classical activation) have long been recognized, but the underlying mechanisms are not well defined. Therefore, we analyzed gene expression profiles of macrophages and identified genes, transcription factors (TFs) and transcription co-factors (TcoFs) that are uniquely or highly expressed in IFN-γ-mediated TLR4 ligand LPS-inducible versus only TLR4 ligand LPS-inducible primary macrophages. This macrophage gene expression has not been observed in macrophage cell lines. We also showed that IL-4 and IL-13 (M2 or alternative activation) elicited the induction of a distinct subset of genes related to M2 macrophage polarization. Importantly, this macrophage gene expression was also associated with promoter conservation. In particular, our approach revealed novel roles for the TFs and TcoFs in response to inflammation. We believe that the systematic approach presented herein is an important framework to better understand the transcriptional machinery of different macrophage subtypes.